Produção de L(+) ácido lático por bactérias láticas utilizando meios com batata - Alves, Mariliana Luiza Ferreira (2014)
Lactic acid (LA) is the final product of lactic acid bacteria (LAB) homofermentation and presents great commercial importance. A few LAB are known for directly converting starch into LA, these are called amylolytic LAB. The L(+) lactic acid isomer, obtained only by fermentation, is the main raw material in the production of a few biodegradable polymers such as polylactide. The potato, rich in starch and vitamins, is a potential feedstock to be used in fermentation processes, since, in Brazil, its production during the stages of harvesting and marketing presents significant loss. Thus, this research aimed at investigating lactic acid production capacity from 5 LAB species (Enterococcus durans, E. faecalis, Lactobacillus plantarum, L. rhamnosus and Streptococcus mutans), using potato mediums (agata cultivar), hydrolyzed or not, studying the effect of enriching the fermentation medium with yeast extract (YE) in order to select the one with highest productivity. In the second stage we used the RCCD 2² full factorial design and surface response methodology to assess the influence, in the fermentation medium, of potato pulp and YE concentrations over L(+) lactic acid productivity and yield using L. rhamnosus. The fermentations were conducted in erlenmeyer flasks at 37 oC /96 h in BOD oven without agitation, and enzyme and HPLC tests were used to qualitatively and quantitatively determine the L(+) lactic acid. Under the evaluation conditions, the studied species showed greater production potential in potato hydrolyzed medium with yeast extract. The increased concentration of YE in the medium caused higher LA production. The highest concentration of L(+) lactic acid achieved was of 25g/L in the fermentation medium with 35 % (m/m) hydrolyzed potato pulp and 8 % (w/v) YE using L. rhamnosus.